Human platelet antigen-3 polymorphism as a risk factor for rheumatological manifestations in hepatitis C - Medolago, Natalia Bronzatto [UNESP]; Ferrasi, Adriana Camargo [UNESP]; Rocha, Oswaldo Melo da [UNESP]; Moura Campos Pardini, Maria Ines de [UNESP]; Tommasini Grotto, Rejane Maria [UNESP]; Galvani, Aline Faria [UNESP]; Silva, Giovanni Faria [UNESP] (Soc Brasileira Medicina Tropical, 2020)
Introduction: Hepatitis C virus (HCV) infection is involved in the pathogenesis of autoimmune and rheumatic disorders. Although the human platelet antigens (HPA) polymorphism are associated with HCV persistence, they have not been investigated in rheumatological manifestations (RM). This study focused on verifying associations between allele and genotype HPA and RM in patients with chronic hepatitis C. Methods: Patients (159) with chronic hepatitis C of both genders were analyzed. Results: Women showed association between HPA-3 polymorphisms and RM. Conclusions: An unprecedented strong association between rheumatological manifestations and HPA-3 polymorphism, possibly predisposing women to complications during the disease course, was observed.
Keywords: Hepatitis C; Human platelet antigens; Polymorphism; Rheumatological manifestations